Effect of Iron Rich Foods SMS Intervention on Iron Intake in Pregnant Women with Anemia - Idris, Nadhirah Ananda; Faradilah, Andi; Ramadhani, Rauly; Fauziah, Henny (Diversity: Disease Preventive of Research Integrity, 2023)
Pregnancy-related anemia has been linked to many undesirable consequences for both mothers and their children. Prevention of anemia in pregnant women can be supported through health promotion media such as SMS-gateway. This study was focused on knowing the effect of SMS gateway knowledge about foods high in iron on intake of foods high in iron in anemic pregnant women. The study was used a double-blind randomized controlled trial to analyze the effect of SMS intervention on iron-rich food on 68 anemic pregnant women at seven health centers in Makassar City. The intervention applied the software Gili SMS® to deliver SMS interventions. The intervention was given on days 3, 10, 17, and 24 of the study, and food recalls were carried out on days 0 and 28 of the study using the 24-hour food recall method. We found that there was no significant difference on intake of iron but a significant difference between intake of energy and carbohydrate between control and intervention group after SMS gateway intervention. By the recommendations in one of the verses in the Qur'an, pregnant women are encouraged to choose and consume good food such as vegetable and animal protein produced by plants and animals. Foods are suitable for the body and provide all the nutrients needed for the body's normal functioning. We found no increased of iron intake after SMS intervention in pregnant women with anemia.